2014
DOI: 10.1111/jmwh.12243
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Care in Ghana: A Critical Review of the Literature

Abstract: The Government of Ghana has taken important steps to mitigate the impact of unsafe abortion. However, the expected decline in maternal deaths is yet to be realized. This literature review aims to present findings from empirical research directly related to abortion provision in Ghana and identify gaps for future research. A total of four (4) databases were searched with the keywords "Ghana and abortion" and hand review of reference lists was conducted. All abstracts were reviewed. The final include sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Therefore, in 1994, the Ministry of Health/GHS expanded its efforts to prevent unsafe abortion to include postabortion care (PAC), which could be provided by midwives as well as physicians …”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in 1994, the Ministry of Health/GHS expanded its efforts to prevent unsafe abortion to include postabortion care (PAC), which could be provided by midwives as well as physicians …”
Section: Contextmentioning
confidence: 99%
“…In 1994, when the GHS embarked on the provision of postabortion care to remedy the morbidity and mortality associated with unsafe procedures, midwives were trained to use manual vacuum aspiration (MVA) . As the law permits abortion provision by any registered medical practitioner, the comprehensive abortion care guidelines specify that midwives can provide first‐trimester abortion procedures using medication abortion as well as MVA; the protocols have since been revised accordingly and mifepristone has been registered in the country.…”
Section: Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their technical content and endorsement proved essential. Participation by the nursing and midwifery societies was key in those countries engaged in task sharing, although some of these were apprehensive about possible loss of turf and they encountered some resistance from members concerned about workload and associated remuneration …”
Section: Recipientsmentioning
confidence: 99%
“…Participation by the nursing and midwifery societies was key in those countries engaged in task sharing, although some of these were apprehensive about possible loss of turf and they encountered some resistance from members concerned about workload and associated remuneration. 31,67,68 In two of the African cases, informants reported that the UN agencies, WHO and UNFPA, had been important partners and that their rigorously developed guidelines for abortion services, including medical abortion, as well as for task sharing had proved highly useful. The Latin American countries studied also drew upon the WHO guidelines, which they modified.…”
Section: Recipientsmentioning
confidence: 99%